The influence of induced moods on aging of phonological encoding in spoken word production: an ERP study - Jia, Lexin; Zhao, Ruiying; Zhang, Qingfang (Frontiers in Human Neuroscience, 2024)
This study investigated the influence of induced mood on the phonological encoding involved in Chinese spoken word production with a picture-word inference task while concurrently recorded electrophysiological signals. In the experiment, young and older participants watched videos for inducing positive, negative, or neutral mood, and then they were instructed to name target picture while ignoring phonologically related or unrelated distractor words. A phonological facilitation effect was observed in young adults but not in older adults, suggesting an age-related decline of phonological encoding. Both groups showed an inhibition effect in negative mood but not in positive mood, suggesting that speakers have different processing styles in different moods. ERP data revealed a phonological effect around the time window of 250-350 ms in both groups. Meanwhile, young adults showed a phonological effect around 350-450 ms in negative mood and positive mood which may reflect self-monitoring in speech production. We suggest that the former effect may reflect phonological encoding while the latter reflects self-monitoring of internal syllables or phonemes. Furthermore, induced moods influence the phonological effect in older and young adults differently. Behavioral and ERP results provide consistent evidence for the aging decline of phonological encoding in spoken word production.